2011
DOI: 10.4196/kjpp.2011.15.4.241
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Mitogenic Activity of a Lectin from Purse Crab Philyra Pisum

Abstract: A lectin from the hemolymph of purse crab, Philyra pisum, was found to have anti-proliferative activity on human lung cancer cells by our laboratory. In this study, P. pisum lectin (PPL) was molecularly characterized including molecular mass, amino acid sequences, amino acid composition, and the effects of metal ions, temperature, and pH on the activity. W e found that PPL showed mitogenic activity on human lymphocytes and BALB/c mouse splenocytes. The mitogenic activity (maximum stimulation index, SI=9.57±0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Hemolymph was prepared from P. pisum and the PPL was purified from this hemolymph as described previously [ 13 , 14 ]. The concentration of the purified lectin was determined by the Bradford assay [ 15 ] using bovine serum albumin (Bio-Rad, Hercules, CA, USA) as the standard.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemolymph was prepared from P. pisum and the PPL was purified from this hemolymph as described previously [ 13 , 14 ]. The concentration of the purified lectin was determined by the Bradford assay [ 15 ] using bovine serum albumin (Bio-Rad, Hercules, CA, USA) as the standard.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous investigation indicated that P. pisum lectin (PPL), which has a molecular mass of 24,060 Da and is obtained from the hemolymph of P. pisum , exhibits hemagglutination and antiproliferative activities in human lung cancer cells [ 13 ]. The molecular characterization of PPL including its molecular mass, p I value, amino acid sequences, amino acid composition, and effects of pH, temperature, and metal ions on its activity as well as mitogenic activities on human lymphocytes were also investigated [ 14 ].…”
Section: Introductionmentioning
confidence: 99%